ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA USAHA KECIL MENENGAH PADA INDUSTRI KERAJINAN ROTAN (Kasus pada UKM Mitra Furniture Rumbai Pekanbaru) - Susana Budita; Meyzi Herianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The purpose of this study was to determine the sources and uses of working capital in the Small and Medium Enterprise Partners Furniture Tassel Pekanbaru by the author which is on Jl. Yos Sudarso Rt 01/02, Meranti Pandak Tassel Pekanbaru. The research concludes seen from the average liquidity ratio is very high and of the working capital turnover Small and Medium Enterprise Partners Furniture has decreased each year in such matters, it is stated that the company is not effective in the management of working capital as well as inventories held. This is due to the substantial investment in cash and stock. In conducting this study is based on analysis of authors published financial data in the financial statements prepared in accordance with accounting principles prevalent. Methods of data analysis using the method is to collect quantitative descriptive data then tabulated and presented in table form hereinafter described and analyzed. Analysis using the formula of working capital liquidity ratios, activity ratios and profitability ratios.Keywords: utilization, working capital, Small and Medium Enterprises